Peran Keluarga Dalam Internalisasi Nilai Akidah Pada Anak Usia Dini Di Era Digital: A Systematic Literature Review - Muhammad Syukri; Muhammad Syahdah Majid; Helma Yunida; Helda Yanti (An-Nafis: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2026)
The internalisation of religious values in early childhood is a cornerstone of character and moral development, especially amid the challenges of the digital era, which is characterised by a flood of information and shifting values. The family, as a child’s primary environment, plays a strategic role in instilling faith values from an early age. However, the development of digital technology presents new challenges, as children no longer receive values solely from their families but also from diverse media that may not always align with Islamic values. Therefore, a study on the role of the family in the internalisation of religious values is essential to understand relevant strategies in the contemporary context. This study aims to analyse the role of the family, strategies for the internalisation of religious values, and their implications for the moral development of young children in the digital era. The method used is a systematic literature review of relevant scientific articles selected based on specific criteria. The results suggest that the family plays a primary role in the internalisation of religious values through modelling, habit formation, and their integration into daily life. In the digital era, this role has evolved into a more complex one, serving as an agent of curation, mediation, and value filtering against external influences. Effective internalisation of religious beliefs has been shown to influence the development of children’s moral reasoning, self-control, and moral resilience.